2021
DOI: 10.3390/app112311544
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Brain State and Behavioral Performance during Repetitive Visual Stimulation

Abstract: We tested whether changes in prestimulus neural activity predict behavioral performance (decision time and errors) during a prolonged visual task. The task was to classify ambiguous stimuli—Necker cubes; manipulating the degree of ambiguity from low ambiguity (LA) to high ambiguity (HA) changed the task difficulty. First, we assumed that the observer’s state changes over time, which leads to a change in the prestimulus brain activity. Second, we supposed that the prestimulus state produces a different effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the effect might depend on task difficulty: longer decision time for an easy task and lower rate of erroneous responses in a difficult task (Kuc et al, 2021). Experiments on monkeys performing somatosensory discrimination tasks with a sequential presentation of stimuli indicate that the decrease of alpha power (in premotor and motor regions) correlates with better discrimination performance (Haegens et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect might depend on task difficulty: longer decision time for an easy task and lower rate of erroneous responses in a difficult task (Kuc et al, 2021). Experiments on monkeys performing somatosensory discrimination tasks with a sequential presentation of stimuli indicate that the decrease of alpha power (in premotor and motor regions) correlates with better discrimination performance (Haegens et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the relationship between alpha power and decision time comes from the experiment of Paluch, Jurewicz, and Wróbel 42 , who analyzed responses among groups of participants responding fast or slowly to a decision task and showed that fast responders had a lower alpha power during the anticipation period. Another experiment 49 showed that the effect of a large alpha power before stimulus onset might depend on task difficulty: longer decision times for an easy task and lower rates of erroneous responses for a difficult task. Experiments on monkeys performing somatosensory discrimination tasks with a sequential presentation of stimuli indicated that a decrease in alpha power (in premotor and motor regions) correlated with better discrimination performance 50 .…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the data for each of the above frequency range, we reassigned the EEG signals (1) to the total average, subtracted the mean, and filtered with a fourth-order Butterworth ( f L , f H )-Hz bandpass filter, where f L and f H are the boundaries of the frequency domain of interest [58]. For example, for the α-range f L = 8 Hz and f H = 12 Hz, and we obtained the alpha-band signal x I,α n .…”
Section: Research Paradigmmentioning
confidence: 99%